Determinants of Individual Taxpayers’ Compliance in Indonesia: A Meta-Analysis - Okta Handayani; Theresia Woro Damayanti (The Indonesian Journal of Accounting Research, 2018)
Abstract: This research presents a meta-analysis towards 31 studies regarding the tax compliance in Indonesia from 2010- 2015. This study examined the influence of the tax's service quality, tax knowledge, taxpayer awareness, tax socialization, tax sanctions and attitudes of taxpayers to the taxpayer compliance in Indonesia. The purpose of this study is to strengthen the findings of previous research that the dependent variable is affecting taxpayer compliance in Indonesia. Used meta-analysis, this study obtained empirical evidence that all the dependent variables are the quality of tax services, tax knowledge, taxpayer awareness, tax socialization, tax sanctions and attitudes of taxpayers positively affects the taxpayer compliance of individuals in Indonesia.Abstrak: Penelitian ini menyajikan meta-analisis terhadap 31 penelitian mengenai kepatuhan pajak di Indonesia dari tahun 2010-2017. Studi ini menguji pengaruh kualitas pelayanan pajak, pengetahuan pajak, kesadaran wajib pajak, sosialisasi pajak, sanksi pajak dan sikap pembayar pajak untuk kepatuhan wajib pajak di Indonesia. Tujuan penelitian ini adalah untuk memperkuat temuan penelitian sebelumnya bahwa variabel dependen mempengaruhi kepatuhan wajib pajak di Indonesia. Dengan menggunakan meta-analisis, penelitian ini memperoleh bukti empiris bahwa semua variabel dependen adalah kualitas jasa perpajakan, pengetahuan pajak, kesadaran wajib pajak, sosialisasi pajak, sanksi pajak dan sikap wajib pajak berpengaruh positif terhadap kepatuhan wajib pajak individu di Indonesia.